2017
DOI: 10.1371/journal.pone.0188034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the suitability of biodegradable rods for use in posterior lumbar fusion: An in-vitro biomechanical evaluation and finite element analysis

Abstract: Interbody fusion with posterior instrumentation is a common method for treating lumbar degenerative disc diseases. However, the high rigidity of the fusion construct may produce abnormal stresses at the adjacent segment and lead to adjacent segment degeneration (ASD). As such, biodegradable implants are becoming more popular for use in orthopaedic surgery. These implants offer sufficient stability for fusion but at a reduced stiffness. Tailored to degrade over a specific timeframe, biodegradable implants could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Previous studies by the authors developed a finite element model of an intact lumbar spine in ANSYS 14.0 (ANSYS Inc., Canonsburg, PA, USA) [17][18][19], including osseoligamentous L1-L5 vertebrae, endplates, intervertebral discs, posterior bony elements, and all 7 ligaments (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by the authors developed a finite element model of an intact lumbar spine in ANSYS 14.0 (ANSYS Inc., Canonsburg, PA, USA) [17][18][19], including osseoligamentous L1-L5 vertebrae, endplates, intervertebral discs, posterior bony elements, and all 7 ligaments (Fig. 1a).…”
Section: Methodsmentioning
confidence: 99%
“…The study of Dreischarf et al [20] also revealed that our finite element models can be used as an improved predictive tool in order to estimate the response of the lumbar spine using different motion input for various cases analyzed. Details of the intact model and its material properties were described in previous studies [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…The contact characteristics between the screw and the cancellous bone and the cortical bone were assumed to be fully bonding, and the contact surface of the other parts was assumed to be frictional contact. The coefficient of friction was set at 0.3 21 .…”
Section: Methodsmentioning
confidence: 99%
“…One reason may be that the process of material degradation will reduce the stiffness of the implants and reduce the high stress value of the implant junction 23 . Tsuang et al 30 used biodegradable materials for posterior spinal fixation; the results showed that when the material degenerated, the same load would increase the deformation of the rod body and reduce the stress concentration. The present study also found that with the degradation of the magnesium alloy, the stress distribution in the proximal femur became closer to that of the intact bone.…”
mentioning
confidence: 99%
“…However, the biodegradable rods had a 20% and 80% decrease in Young's modulus after 6 months and 12 months. 48 Furthermore, both of these studies were done not done in human trials or under true biological conditions, thus not all the effects of wear and tear could be measured and tested.…”
Section: Rodsmentioning
confidence: 99%